From Imaging Data to Cranioplasty Implant Designs - Asmaria, Talitha; Zain, Andi Justike Mahatmala; Pramesti, Arindha Reni; Marzuki, Azwien Niezam Hawalie; Utomo, Muhammad Satrio (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA, 2023)
The cranioplasty procedure is starting from removal the skull bone defects and replacing them with any biocompatible material, such as polymer, ceramic, or titanium alloy. The complication of the surgery as well as the high cost from several material selection required a simulation. Besides that, the case of cranial defects sometimes required a customized design. The presence of three-dimensional (3D) printing technology would be a promising tool to improve the success rate. Prior to 3D printing, the model needs to be corrected from the initial patient’s imaging data to the intended implant design. However, previous related literatures were almost not informing the specific image processing steps to gain the models, while not all operators could understand this sophisticated technique. The study aims to design an implant bone for cranioplasty purpose. The data were processed through the very clear step-by-step image processing stages, three-dimensional (3D) printing, and its evaluation through biomechanical simulation. Quantitatively, the designed cranioplasty implant could deal with the load in the actual application. Qualitatively, the prototypes have matched if applied to the host of cranium bone. In conclusion, although image processing and refinements are the most complicated process, the whole explanation indicate that the provided precise methodology could be a major reference to the similar procedure.